Endometriosis and Beta-hCG > 775 IU/l Increase the Risk of Non-tube-preserving Surgery for Tubal Pregnancy - Nicolaus, Kristin; Jimenez-Cruz, Jorge; Bräuer, Dominik Michael; Lehmann, Thomas; Mothes, Anke Regina; Runnebaum, Ingo B. (Geburtshilfe und Frauenheilkunde, 2018)
Introduction Tubal pregnancy is the most clinically relevant form of ectopic pregnancy. Surgery consisting of laparoscopic salpingotomy is the therapeutic gold standard. This study looked at risk factors for non-tube-preserving surgery. The aim was to determine a cut-off value for beta-hCG levels, which could be used to predict the extent of tubal surgery.Materials and Method 97 patients with tubal pregnancy who underwent primary salpingotomy in the Department of Gynecology and Obstetrics of Jena University Hospital between 2010 and 2016 were retrospectively analyzed. A prior medical history of risk factors such as adnexitis, ectopic pregnancy, tubal surgery, treatment for infertility and intrauterine pessary was included in the analysis. The study population was divided into two subgroups: (1) a group which underwent laparoscopic linear salpingotomy, and (2) a group which had laparoscopic partial tubal resection or salpingectomy. Risk factors for salpingectomy were determined using binary logistic regression analysis. Statistical analysis was done using SPSS, version 24.0, to identify risk factors for non-tube-preserving surgery.Results 68 patients (70.1%) underwent laparoscopic salpingotomy and 29 patients (29.9%) had laparoscopic salpingectomy. The two groups differed with regard to age (p = 0.01) but not with regard to the parameters ‘gestational age’, ‘viability and rupture status of the ectopic pregnancy’ or ‘symptoms at presentation’. Patients who were known to have endometriosis prior to surgery or who were diagnosed with endometriosis intraoperatively were more likely to undergo salpingectomy (OR: 3.28; 95% CI: 0.9 – 10.8; p = 0.05). Calculated mean beta-hCG levels were higher in the salpingectomy group compared to the group who had tube-preserving salpingotomy (3277.8 IU/l vs. 9338.3 IU/l, p = 0.01). A cut-off beta-hCG value of 775 IU/l prior to surgery was predictive for salpingectomy with a true positive rate of 86.2% and increased the probability that salpingectomy would be necessary (OR: 5.23; 95% CI: 0.229 – 0.471; p = 0.005).Conclusion Endometriosis and a beta-hCG value of more than 775 IU/l significantly increased the risk for non-tube-preserving surgery in women with tubal pregnancy.
Keywords: endometriosis; tubal pregnancy; beta-hCG; salpingotomy; salpingectomy